2022
DOI: 10.1159/000524802
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Role in the Development of Borderline Personality Disorder

Abstract: The progressively improving understanding of the borderline personality disorder (BPD) has led to an increased interest in the better clarification of the integrated role of biological and psychosocial factors in the underlying pathophysiology of this condition. The influence of early childhood interactions and stress exposure in shaping our personalities during adulthood cannot be emphasized enough. In this review, we discuss the critical role of parenting-related factors including maladaptive parenting, pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Because of this, we can further suppose the different parenting styles between mother and father may be associated with personality. The identified associations between parenting styles and borderline personality disorder also could imply the associations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, we can further suppose the different parenting styles between mother and father may be associated with personality. The identified associations between parenting styles and borderline personality disorder also could imply the associations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the most common correlation between giving antidepressants to individuals with BPD is comorbidity for affective disorders [26]. Early childhood impacts on the development of BPD's psychopathology include parenthood-related issues such as dysfunctional parenting, parenting philosophies, and parenting psychopathology [27]. Staged therapy designs, additional treatments, and technology-based interventions could be beneficial in cases where developing cost-effective interventions is necessary when people are newly diagnosed or are awaiting full-package therapy (or both) or when a particular deficit needs to be addressed in the context of ongoing treatment [28].…”
Section: Treatment Of Borderline Personality Disordermentioning
confidence: 99%